Strega Nona : an old tale - De Paola, Tomie (New York : Scholastic, 1991)
When Strega Nona leaves him alone with her magic pasta pot, Big Anthony is determined to show the townspeople how it works.
Keywords: Folklore -- Italy; Folklore -- Italy; Big books